(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Currently, the energy meter is installed in residential or business locations to gather information on the amount of energy used, which is then shown on either a traditional dial or a digital screen. At the conclusion of each billing cycle, a representative from the service provider must physically visit the location where the meter is installed in order to get the reading and record it for the purpose of generating the subsequent bill. The current energy billing system is both flawed and time-consuming. The objective of this project is to create an energy meter that can measure the amount of power utilized by the user in kilowatt-hours (kWh). Additionally, it will provide real-time monitoring of consumption, eliminating the need for meter readers to visit each customer to collect data and deliver bill slips. The energy consumption is determined by measuring the voltage and current. In addition, it consistently monitors the energy meter readings and autonomously transmits notifications such as low-balance alert, zero-balance alert, and recharging alert to the registered phone via a GSM modem. Anomalies in the use of electricity have been noticed and an alarm message is promptly sent to the authorities. The Arduino code does power and energy calculations, and sends a message to the respective customer indicating their unit use and the amount of their bill.